Life itself [videorecording (DVD)] - Ebert, Roger; Ebert, Chaz; Ebert, Roger (Magnolia Home Entertainment, 2015)
The legacy of Roger Ebert's life, recounts the inspiring and entertaining life of the world-renowned film critic and social commentator, from his Pulitzer Prize-winning film criticism at the Chicago Sun-Times to becoming one of the most influential cultural voices in America.